1999
DOI: 10.1590/s1020-49891999000400006
|View full text |Cite
|
Sign up to set email alerts
|

Estudio multicéntrico sobre actitudes y normas culturales frente a la violencia (proyecto ACTIVA): metodología

Abstract: The purpose of this article is to describe the conceptual bases and methods used in the ACTIVA multicenter study, as well as the process employed in the different stages of the research. General information is given on the approach, design, and methods that were applied in the cities that participated in the study: San Salvador, El Salvador; San José, Costa Rica; Cali, Colombia; Caracas, Venezuela; Salvador, Bahia, Brazil; Rio de Janeiro, Brazil; Santiago, Chile; and Madrid, Spain. The objectives of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
1
8
0
5
Order By: Relevance
“…*** Even higher rates were obtained using the CBCL in a subsample of children and adolescents (n=38; 7-11 years) referred to a child psychiatry intake service in Rio de Janeiro, also in Southeastern Brazil: 92.1% prevalence including clinical (84.2%) and borderline cases (7.9%). **** Our results regarding child-rearing attitudes slapping or hitting with a belt were compatible with the data from a survey 8 conducted in Latin-American countries. This survey registered similar rates of slapping administered by mothers and fathers in Rio de Janeiro (11.9% and 33.8%, respectively) and of hitting children with a hard object by mothers and fathers in Salvador, Northeastern Brazil (7.9% and 11.8%, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…*** Even higher rates were obtained using the CBCL in a subsample of children and adolescents (n=38; 7-11 years) referred to a child psychiatry intake service in Rio de Janeiro, also in Southeastern Brazil: 92.1% prevalence including clinical (84.2%) and borderline cases (7.9%). **** Our results regarding child-rearing attitudes slapping or hitting with a belt were compatible with the data from a survey 8 conducted in Latin-American countries. This survey registered similar rates of slapping administered by mothers and fathers in Rio de Janeiro (11.9% and 33.8%, respectively) and of hitting children with a hard object by mothers and fathers in Salvador, Northeastern Brazil (7.9% and 11.8%, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…There was no significant difference between men and women among 1114 adults in Rio de Janeiro (Orpinas, 1999; see Table 2, Sample B).…”
Section: Resultsmentioning
confidence: 94%
“…The only study examining theft reported a 5% prevalence of stealing at school in the previous year (Abramovay, 2012). In two household surveys of adults (18–70 year olds), the prevalence of hitting a non-family member in the previous year was 5.6% and 2.5% (Orpinas, 1999: samples A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta importante diferencia entre la presencia de agresión sexual y agresión física, puede deberse a que en el Perú, la agresión física se asume como un evento cotidiano que forma parte de la educación tradicional (10,13,14) ; por ejemplo, algunos estudios señalan que entre el 40 a 50% de los padres en Lima agrede físicamente a sus hijos (14,15) . A diferencia de la agresión sexual que es un evento dramático culturalmente inaceptable; por ello, a pesar del subregistro (indeterminado para Perú) la agresión sexual es denunciada con frecuencia.…”
Section: Discussionunclassified